(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Industrial dust assessment systems for industrial dust, which are available in a number of foreign countries, differ from those adopted. Currently, there is no reliable way to calculate the risk of explosion of dust based on their composition, heat of combustion and other physicochemical properties. If subsequent studies do not theoretically predict the level of dust hazard, experimental measurements will be required. Industrial dust for explosion hazard has been tested in laboratory methods and officially approved in foreign countries. These methods differ from each other because they are largely independently developed and their international standardization has not yet been carried out